2001
DOI: 10.5194/aab-44-193-2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary organic selenium and vitamin E supplementation on post mortem oxidative deterioration in muscles of pigs

Abstract: Abstract. The effect of feeding high levels of α-tocopherol and organic selenium (Se) to pigs on colour stability and on the susceptibility to oxidative deterioration was investigated. Treatments consisted of supplementation of vitamin E (200 mg/kg diet), organic Se (0.3 mg/kg diet) and both vitamin E and organic Se for the last 60 days to finishing pigs before slaughtering. Longissimus dorsi (LD) and psoas major (PM) muscles were examined after 2 and 7 days of storage on colour stability and on lipid peroxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The differences in colour (reflectance %) and conductivity values measured 24 h post mortem were also insignificant (P > 0.05), which is in agreement with the results reported by Krska et al (2001) where colour stability (MLLT, 7 day storage) was unaffected by the administration of higher levels of vitamin E and Se. Drip loss of MLLT during the 48 h measurement period tended to be lower when the higher level Se was fed.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The differences in colour (reflectance %) and conductivity values measured 24 h post mortem were also insignificant (P > 0.05), which is in agreement with the results reported by Krska et al (2001) where colour stability (MLLT, 7 day storage) was unaffected by the administration of higher levels of vitamin E and Se. Drip loss of MLLT during the 48 h measurement period tended to be lower when the higher level Se was fed.…”
Section: Resultssupporting
confidence: 81%
“…The effects of organic and inorganic Se on pigs have been studied frequently (Goehring et al, 1984;Mahan and Parret, 1996;Mahan et al, 1999;Kim and Mahan, 2001;Krska et al, 2001;Nürnberg et al, 2002). The results indicated that the major carcass measurements did not seem to be affected by the dietary Se levels or sources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that vitamin E supplementation has a beneficial effect on the quality of meat (Monahan et al, 1994;Guo et al, 2006), and in combination with Se it may be more effective in improving the antioxidative defense system of cells and tissues (Krska et al, 2001). Oxidative processes in animal muscles are major factors involved in the deterioration of meat quality.…”
Section: Introductionmentioning
confidence: 98%
“…Lipid peroxidation and cellular antioxidant defence, including reduced glutathione content and glutathione-peroxidase activity, have importance in the oxidative stability of pork (Krska et al 2001), because glutathione peroxidase reduces hydrogen peroxide and lipid hydroperoxides, potentially harmful pro-oxidants that may promote peroxidation of polyunsaturated phospholipids in biological membranes. Importance of reduced glutathione is supported by those findings that the magnitude of muscle protein turnover depends on, among other factors, the actual glutathione supply (Śliwa-Jóźwik et al 2002).…”
Section: Introductionmentioning
confidence: 99%